Meningococcal vaccination in primary care amongst adolescents in North West England: an ecological study investigating associations with general practice characteristics. (27th January 2018) - Blagden, Sarah; Hungerford, Daniel; Limmer, Mark
Abstract: Background: In 2015 the meningococcal ACWY (MenACWY) vaccination was introduced amongst adolescents in England following increased incidence and mortality associated with meningococcal group W. Methods: MenACWY vaccination uptake data for 17–18 years old and students delivered in primary care were obtained for 20 National Health Service clinical commissioning groups (CCGs) via the ImmForm vaccination system. Data on general practice characteristics, encompassing demographics and patient satisfaction variables, were extracted from the National General Practice Profiles resource. Univariable analysis of the associations between practice characteristics and vaccination was performed, followed by multivariable negative binomial regression. Results: Data were utilized from 587 general practices, accounting for ~8% of all general practices in England. MenACWY vaccination uptake varied from 20.8% to 46.8% across the CCGs evaluated. Upon multivariable regression, vaccination uptake increased with increasing percentage of patients from ethnic minorities, increasing percentage of patients aged 15–24 years, increasing percentage of patients that would recommend their practice and total Quality and Outcomes Framework achievement for the practice. Conversely, vaccination uptake decreased with increasing deprivation. Conclusions: This study has identified several factors independently associated with MenACWY vaccination in primary care. These findings will enable a targeted approach to improve general practice-level vaccination uptake.